2015
DOI: 10.1155/2015/974568
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Pars Plana Vitrectomy with and without Internal Limiting Membrane Peeling for Idiopathic Retinal Membrane Removal: A Meta-Analysis

Abstract: We conducted a meta-analysis of published retrospective studies and compared the effectiveness of pars plana vitrectomy with and without internal limiting membrane (ILM) peeling for idiopathic epiretinal membrane (IERM). The results revealed that patients in the IERM+ILM peeling group had better BCVA after surgery within 12 months than those in IERM peeling group. But patients in the IERM peeling group showed better BCVA in the 18th month. More retrospective studies or randomized controlled trials are required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…Visual acuity findings in our meta-analysis are likely explained by the fact that additional ILM peeling provided no improvement in functional outcomes, these findings were in consistent with the previous review,39 but contrast to a recent meta-analysis,40 which revealed that ILM peeling group had better BCVA after surgery within 12 months, but worse BCVA in the 18th month.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Visual acuity findings in our meta-analysis are likely explained by the fact that additional ILM peeling provided no improvement in functional outcomes, these findings were in consistent with the previous review,39 but contrast to a recent meta-analysis,40 which revealed that ILM peeling group had better BCVA after surgery within 12 months, but worse BCVA in the 18th month.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, we found a meta-analysis about this topic that was published on 26 November 2015 40. There are some disagreements between our review and this paper.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, two meta-analyses reported results of ERM and ILM peeling compared to ERM peeling alone, coming to different results. While one meta-analysis reported BCVA to be better in the ERM and ILM peeling group within 12 months after surgery, but BCVA to be better in the ERM peeling group in the 18th month [34], the other meta-analysis reported BCVA to be better in the ERM peeling group within 12 months after surgery and BCVA to be better in the ERM and ILM peeling group after 18 months after surgery [35]. The ERM peeling group without ILM peeling showed higher reduction in central retinal thickness, but also higher ERM recurrence rates [35].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of its existence is not yet clear. However, it has been attributed mostly to posterior vitreous detachment (PVD) [1], which provokes glial cells (Muller) and extracellular components to accumulate and migrate on the ILM [2]. The prevalence of ERM ranges from 1.02% to 18.5% [3].…”
Section: Introductionmentioning
confidence: 99%
“…Triamcinolone, indocyanine green and triphenylmethane (brilliant blue) are dyes which can be used during the operation [2]. The rate of recurrence of ERM formation is 10%-16.3% [1]. It is usual for the ILM to be peeled because it acts like a scaffold for cells' proliferation on the macula.…”
Section: Introductionmentioning
confidence: 99%